Prevention of occupational asthma. - Venables, K (1994)
This paper focuses on the prevention of asthma caused by exposure to sensitizing agents in the workplace. Control of exposure (primary prevention) is the most direct method of reducing the number of incident cases. Screening programmes are also necessary as a "safety net", and have value as secondary prevention, because early detection may improve long-term prognosis. It is recommended that regulatory or advisory bodies with responsibility for occupational asthma publish a guidance document on occupational asthma explaining their current concepts. Surveillance activities provide information on how common asthma is relative to other occupational lung diseases, and on the relative frequency of occurrence of asthma caused by different agents. Publication of a list of sensitizing agents would aid those with responsibility for control of exposure in the workplace. Epidemiological research on exposure-response relations is is necessary as a background to prevention. This paper recommends such studies. Immunotoxicological research also has a role in testing hypotheses that cannot be tested in human subjects. Some standardization of screening programmes in industry is desirable. A short symptoms questionnaire is economical and acceptable to workers, but there are other approaches. Finally, evaluative research on prevention measures gives information on their effectiveness and efficiency.